2021
DOI: 10.1098/rspa.2020.0519
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting imperfect interface laws for two-dimensional elastodynamics

Abstract: We study the interaction of in-plane elastic waves with imperfect interfaces composed of a periodic array of voids or cracks. An effective model is derived from high-order asymptotic analysis based on two-scale homogenization and matched asymptotic technique. In two-dimensional elasticity, we obtain jump conditions set on the in-plane displacements and normal stresses; the jumps involve in addition effective parameters provided by static, elementary problems being the equivalents of the cell problems in classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…1) Zero-order problem: As for the film, inserting (29) in (1) along with (30) provides equations at the dominant order O( 1 ). In particular, we obtain for h 0 the set of equations 8 > > < > > :…”
Section: B Asymptotic Analysis For a Metafilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) Zero-order problem: As for the film, inserting (29) in (1) along with (30) provides equations at the dominant order O( 1 ). In particular, we obtain for h 0 the set of equations 8 > > < > > :…”
Section: B Asymptotic Analysis For a Metafilmsmentioning
confidence: 99%
“…This could be an incidental remark but it turns out that these approximate problems can be discriminated in terms of their well-posedness or stability. Up to now, this problem has been addressed in the context of metafilms in elastodynamics [29], [30] and in acoustics [31], [32] and it has been shown that unstable formulations may foster numerical instabilities in the time domain. Such instabilities have been reported in [33] for homogeneous thin films, and in [34], [35] for structured thin films.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have been used in static elasticity [6,7]. For the propagation of waves, they have been adapted in elasticity, studies have focused on rows of non-resonant inclusions [8,9] then on resonant inclusions [10]. For the propagation of waves in electromagnetism [11][12][13], and in acoustics [5,14].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the acoustic problems with a standing fluid, similar treatment was employed to study the electromagnetic field [11]. Using higher order approximation involving the correctors at order o(ε 1 ), nontrivial interface conditions capturing acoustic impedance of the thin interfaces have been obtained in [12,13] using an approach based on the so-called inner and outer asymptotic expansions which enable to treat rather general shapes of the perforations, or other heterogeneities.…”
Section: Introductionmentioning
confidence: 99%